Inovasi dan Adaptasi dalam Ruang Lingkup Manajemen Pendidikan Perspektif Al-Qur’an - Arif, Miftakhul (Fakultas Ushuluddin dan Dakwah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2024)
The current Islamic education system in Indonesia still has questions about the position and competence of its graduates, who are less able to compete with the quality of graduates from other institutions that really pay attention to educational issues. Therefore, Islamic educational institutions must improve. One of the improvements that needs to be made is the management of Islamic education. This article was written in an attempt to make a conceptual study of how innovation and adaptation of Islamic education management are to technological developments. This article is a type of qualitative research with a library research approach. The results of the analysis show that the direction of innovation and transformation of Islamic education management as a step of change includes planning, organizing, mobilizing and supervising through cooperation carried out effectively, efficiently and productively to achieve mutually determined goals. Islamic educational institutions should ensure human resources, in this case teachers as the spearhead of the educational process, can be the main priority and short-term goal for every educational institution. So that in a short time, each educational institution can ensure that it has human resources (teachers) who have competence in accordance with the needs and developments of the times.